Traumatic Axonal Injury Induces Proteolytic Cleavage of the Voltage-Gated Sodium Channels Modulated by Tetrodotoxin and Protease Inhibitors - Iwata, Akira (J Neurosci, 2004)
We demonstrated previously that dynamic stretch injury of cultured axons induces structural changes and Ca(2+) influx modulated by tetrodotoxin (TTX)-sensitive voltage-gated sodium channels (NaChs). In the present study, we evaluated potential damage to the NaCh α-subunit, which can cause noninactivation of NaChs. In addition, we explored the effects of pre-injury and post-injury treatment with TTX and protease inhibition on proteolysis of the NaCh α-subunit and intra-axonal calcium levels ([Ca(2+)]i) over 60 min after trauma. After stretch injury, we found that [Ca(2+)]i continued to increase in untreated axons for at least 60 min. We also observed that the III-IV intra-axonal loop of the NaCh α-subunit was proteolyzed between 5 and 20 min after trauma. Pre-injury treatment of the axons with TTX completely abolished the posttraumatic increase in [Ca(2+)]i and proteolysis of the NaCh α-subunit. In addition, both pre-injury and post-injury inhibition of protease activity attenuated long-term increases in [Ca(2+)]i as well as mitigating degradation of the NaCh α-subunit. These results suggest a unique “feed-forward” deleterious process initiated by mechanical trauma of axons. Na(+) influx through NaChs resulting from axonal deformation triggers initial increases in [Ca(2+)]i and subsequent proteolysis of the NaChα-subunit. In turn, degradation of the α-subunit promotes persistent elevations in [Ca(2+)]i, fueling additional pathologic changes. These observations may have important implications for developing therapeutic strategies for axonal trauma.